Pitaya as a New Alternative Crop for Iberian Peninsula: Biology and Edaphoclimatic Requirements - Trindade, Ana Rita; Paiva, Paulo; Lacerda, Vander [UNESP]; Marques, Natália; Neto, Luís; Duarte, Amílcar (MDPI, 2023)
Pitaya is one of the fruit species whose demand has increased in recent years due to the numerous health benefits and lucrative price of the fruit and its by-products. In Europe, the Iberian Peninsula and other Mediterranean countries are the ones with favorable climatic conditions for its cultivation. This document describes much of the history of pitaya in the Iberian Peninsula and the difficulties related to its cultivation. A bibliographical survey was carried out on the culture of pitaya in the world, focusing on the edaphoclimatic requirements, and on the possibility of this becoming a consolidated crop in the Iberian Peninsula. The relatively low water requirement of pitaya makes this crop sustainable among crops that require irrigation. In addition, we provide a perspective for use and research of this emerging crop. There has been an exponential growth of scientific publications on pitaya in the last decade; however, much more needs to be researched to know how to increase productivity as well as the sensory quality of fruits in different regions. This sustainable crop is a good option to diversify fruit production in the Iberian Peninsula.
Keywords: Cactaceae; dragon fruit; Europe; review; Selenicereus